Nanoscale Porphyrin Metal-Organic Frameworks Deliver siRNA for Alleviating Early Pulmonary Fibrosis in Acute Lung Injury - Weng, Changmei; Li, Guanhua; Zhang, Dongdong; Duan, Zhaoxia; Chen, Kuijun; Zhang, Jieyuan; Li, Tao; Wang, Jianmin (Frontiers in Bioengineering and Biotechnology, 2022)
Acute lung injury (ALI) has high mortality and still lacks novel and efficient therapies. Zinc finger E-box binding homeobox 1 and 2 (ZEB1/2) are highly expressed in the early stage of ALI and are positively correlated with the progression of pulmonary fibrosis. Herein, we developed a nanoscale Zr(IV)-based porphyrin metal-organic (ZPM) framework to deliver small interfering ZEB1/2 (siZEB1/2) to alleviate early pulmonary fibrosis during ALI. This pH-responsive nano-ZPM system could effectively protect siRNAs during lung delivery until after internalization, and rapidly trigger siRNA release under the mildly acidic environment of the endo/lysosome (pH 4.0-6.5) for transfection and gene silencing. Furthermore, the in vivo studies confirmed that this nano-ZPM system could anchor in inflamed lungs. Moreover, the ZEB1/2 silencing led to increased E-cadherin and decreased α-SMA levels. Overall, the nano-ZPM system was an excellent non-viral vector system to deliver siRNAs to alleviate early pulmonary fibrosis during ALI.